2011
DOI: 10.1007/s11430-011-4324-9
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of the northwestern sub-basin, South China Sea: Results from a wide-angle seismic experiment

Abstract: The crustal structure of the northwestern sub-basin area of the South China Sea was modeled by inverting a wide-angle seismic survey line across the entire region and on both sides of its bounding continental margins. The survey line extended over 484 km. A total of 14 Ocean Bottom Seismometers (OBS) were deployed at intervals of 30 km to record air-gun array sources with a combined volume of 5160 in 3 . The crustal velocity structure of the northwestern sub-basin area was acquired through the integration of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 23 publications
2
51
1
Order By: Relevance
“…[] and Wu et al . [] also found there is no HVL beneath the lower crust according to the OBS2006‐1 velocity profile across the western portion of the Pearl River Mouth Basin (PRMB), the Northwest Sub‐basin, the Zhongsha Islands (Macclesfield Bank) and extending to the East Sub‐basin (supporting information Figure S1a). Interestingly, recent studies based on the seismic profiles and gravity modeling show that there is about 2–4 km thick HVL beneath the lower crust in the Qiongdongnan Basin (QDNB) [ Qiu et al ., ; Zhao et al ., ].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…[] and Wu et al . [] also found there is no HVL beneath the lower crust according to the OBS2006‐1 velocity profile across the western portion of the Pearl River Mouth Basin (PRMB), the Northwest Sub‐basin, the Zhongsha Islands (Macclesfield Bank) and extending to the East Sub‐basin (supporting information Figure S1a). Interestingly, recent studies based on the seismic profiles and gravity modeling show that there is about 2–4 km thick HVL beneath the lower crust in the Qiongdongnan Basin (QDNB) [ Qiu et al ., ; Zhao et al ., ].…”
Section: Introductionmentioning
confidence: 87%
“…However, these seamounts including the fossil ridge are surrounded by the oceanic crust, and so the density at depth would likely be similar to that of oceanic crust (2.90 g/cm 3 ). We note that the OBS2006‐1 refraction profile near MCS profile L1 detected a similar fossil ridge with a P‐wave velocity of 5.8–6.8 km/s in the Northwest Sub‐basin [ Wu et al ., ; Ding et al ., ]. The fossil ridge has two layers including an upper layer with a P‐wave velocity of 5.8–6.6 km/s and a lower layer with a P‐wave velocity of 6.6–6.8 km/s.…”
Section: Crustal Structure On the Northwestern Margin Of The South Chmentioning
confidence: 99%
See 1 more Smart Citation
“…It has shown that the middle and eastern part of the northern margin of SCS is of volcanic type with a high velocity layer in the lower crust, the thick high velocity body beneath Dongsha islands in particular, that was interpreted as magma underplating or intruded mantle Wei et al, 2011aWei et al, , 2011bYan et al, 2001;Zhao et al, 2010). While no high velocity layer in the lower crust has been found in the OBS seismic models in the western part of the northern margin of SCS (Qiu et al, 2001;Wu et al, 2011). On the southern margin of SCS, it has shown that the middle and eastern parts of Nansha Block have similar tectonic characters with crust thickness of 20 km in continent and 5-6 km in basin without high velocity layer in the lower crust (Pichot et al, 2014;Qiu et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…More accurate and reliable results of crustal structure were from active wide-angle seismic experiments but only in the northern margin of SCS [10][11][12][13][14][15][16][17]. In recent years several ocean bottom seismometer (OBS) experiments in the southern margin of SCS have been carried out that greatly improved the active seismic data distribution in SCS (Figure 1).…”
mentioning
confidence: 99%